Significance of CO(2 )donor on the production of succinic acid by Actinobacillus succinogenes ATCC 55618 - Zou, Wei (BioMed Central, 2011)
BACKGROUND: Succinic acid is a building-block chemical which could be used as the precursor of many industrial products. The dissolved CO(2 )concentration in the fermentation broth could strongly regulate the metabolic flux of carbon and the activity of phosphoenolpyruvate (PEP) carboxykinase, which are the important committed steps for the biosynthesis of succinic acid by Actinobacillus succinogenes. Previous reports showed that succinic acid production could be promoted by regulating the supply of CO(2 )donor in the fermentation broth. Therefore, the effects of dissolved CO(2 )concentration and MgCO(3 )on the fermentation process should be investigated. In this article, we studied the impacts of gaseous CO(2 )partial pressure, dissolved CO(2 )concentration, and the addition amount of MgCO(3 )on succinic acid production by Actinobacillus succinogenes ATCC 55618. We also demonstrated that gaseous CO(2 )could be removed when MgCO(3 )was fully supplied. RESULTS: An effective CO(2 )quantitative mathematical model was developed to calculate the dissolved CO(2 )concentration in the fermentation broth. The highest succinic acid production of 61.92 g/L was obtained at 159.22 mM dissolved CO(2 )concentration, which was supplied by 40 g/L MgCO(3 )at the CO(2 )partial pressure of 101.33 kPa. When MgCO(3 )was used as the only CO(2 )donor, a maximal succinic acid production of 56.1 g/L was obtained, which was just decreased by 7.03% compared with that obtained under the supply of gaseous CO(2 )and MgCO(3). CONCLUSIONS: Besides the high dissolved CO(2 )concentration, the excessive addition of MgCO(3 )was beneficial to promote the succinic acid synthesis. This was the first report investigating the replaceable of gaseous CO2 in the fermentation of succinic acid. The results obtained in this study may be useful for reducing the cost of succinic acid fermentation process.